Evaluating Liturgical Engagement With Psalms of Lament: Reading Psalm 74 Through the Lenses of Feeling and Thinking - Francis, Leslie J. (Pastoral psychology, 2025)
Recent trends in biblical scholarship that have generated new interest in the book of Psalms and in the voice of lamentation may in turn present new opportunities for the liturgical use of psalms of lament. Drawing on the SIFT approach to biblical hermeneutics, the present study tested the ways in which feeling types and thinking types may evaluate Psalm 74 differently. The data demonstrated that feeling types and thinking types approach a psalm of lament in quite different ways. For thinking types, this is a satisfying intellectual exercise. They are caught up by the theological questions raised and fascinated by the capacity of the human mind to challenge God to keep God’s side of the covenantal agreement with the people. For feeling types, this is a journey of the heart as they identify with the protagonists rehearsing the source and cause of their pain. Preachers and liturgists need to be aware of this contrast.